Communicating abstract meaning: concepts revealed in words and gestures. (18th June 2018) - Zdrazilova, Lenka; Sidhu, David M.; Pexman, Penny M.
Abstract : Abstract words refer to concepts that cannot be directly experienced through our senses (e.g. truth, morality ). How we ground the meanings of abstract words is one of the deepest problems in cognitive science today. We investigated this question in an experiment in which 62 participants were asked to communicate the meanings of words (20 abstract nouns, e.g. impulse ; 10 concrete nouns, e.g. insect ) to a partner without using the words themselves (the taboo task). We analysed the speech and associated gestures that participants used to communicate the meaning of each word in the taboo task. Analysis of verbal and gestural data yielded a number of insights. When communicating about the meanings of abstract words, participants' speech referenced more people and introspections. In contrast, the meanings of concrete words were communicated by referencing more objects and entities. Gesture results showed that when participants spoke about abstract word meanings their speech was accompanied by more metaphorical and beat gestures, and speech about concrete word meanings was accompanied by more iconic gestures. Taken together, the results suggest that abstract meanings are best captured by a model that allows dynamic access to multiple representation systems. This article is part of the theme issue 'Varieties of abstract concepts: development, use and representation in the brain'.